Chromosomal Instability and Origin of B Chromosomes in the Amazonian Glass Tetra Moenkhausia oligolepis (Günther, 1864) (Characiformes, Characidae) - Dos Santos, Luana Pereira; Francisco, Carine M.; Campos Júnior, Edimar O.; Castro, Jonathan P.; Utsunomia, Ricardo; Morelli, Sandra; Porto-Foresti, Fábio [UNESP]; Foresti, Fausto [UNESP]; Artoni, Roberto F. (My University, 2021)
B chromosomes occur in different species of the small characid fishes of the genus Moenkhausia. These supernumerary elements, that do not recombine with chromosomes of the standard A complement and follow their own evolutionary mechanism vary in number, morphology, and distribution. Here, we show karyotypic data of individuals of 2 populations of Moenkhausia oligolepis of the Brazilian Amazon (Pedro Correia and Taboquinha streams, Tocantins river basin), both with a diploid number of 50 chromosomes and karyotypic formula of 10m + 32sm + 8a. In addition to the normal complement, we also observed the occurrence of B chromosomes in the 2 populations with intra- A nd interindividual variation ranging from 0 to 10 Bs, independent of sex. The C-banding pattern evidenced heterochromatic blocks located mainly in the pericentromeric region of the chromosomes, while the B chromosomes appeared euchromatic. Silver-stained nucleolus organizer regions were identified in multiples sites, and some of these blocks were positive when stained with chromomycin A3. The karyotype analysis and the application of whole-chromosome painting in populations of M. oligolepis reinforce the conservation of the basal diploid number for the genus, as well as the evolutionary tendency in these fishes to carry B chromosomes. Both populations turned out to be in different stages of stability and expansion of their B chromosomes. We further suggest that the origin of these chromosomes is due to the formation of isochromosomes. Here, we identified a pair of complement A chromosomes involved in this process.
Keywords: B chromosome; Chromosome painting; Heterochromatin; rDNA; Tetra fish